2010
DOI: 10.3109/03014460.2010.536572
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient deficiency disorders among the rural children of West Bengal, India

Abstract: Micronutrient deficiencies were found to be of public health significance among rural children of West Bengal. Therefore, there is a need to initiate sustainable long-term interventions for prevention and control of micronutrient deficiencies in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
2
22
2
Order By: Relevance
“…Table 3 summarizes odd ratios for caste differentials in nutritional deficiencies (Anaemia and vitamin A deficiency) as reported in three studies. 5,3,4 After adjusting for socio-economic factors in a logistical regression analysis conducted between caste and nutritional indicators of BMI and Anemia, clear caste based differentials persisted. Table 4 summarizes the state based variation in odd ratios for caste differentials in body mass index and anemia.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarizes odd ratios for caste differentials in nutritional deficiencies (Anaemia and vitamin A deficiency) as reported in three studies. 5,3,4 After adjusting for socio-economic factors in a logistical regression analysis conducted between caste and nutritional indicators of BMI and Anemia, clear caste based differentials persisted. Table 4 summarizes the state based variation in odd ratios for caste differentials in body mass index and anemia.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the present study was carried out by the National Nutrition Monitoring Bureau (NNMB) among rural pre-school children in eight states during [2002][2003][2004][2005]. Part of the data of the study pertaining to the states of Maharashtra, West Bengal and Madhya Pradesh has been published elsewhere (23)(24)(25)(26) . An attempt has been made in the present paper to arrive at the national estimates on the prevalence and determinants of VAD.…”
mentioning
confidence: 99%
“…18 Similar study in West Bengal the consumption of adequately iodized salt was 55% at household level and in previous year's baseline survey of Chhattisgarh state was in range of 51-71%. 4,16 NFHS-3 report showed that 51% of the country was using adequately iodized salt (>15 ppm). 19 In a study by Kamat et al in Belgaum, 50 % of households are consuming adequately iodized salt.…”
Section: Discussionmentioning
confidence: 99%
“…1 Base on nationwide survey done by ICMR no state is free from Iodine deficiency and are 'at risk' of developing IDD in India. 4 Based on Iodized salt coverage around 350 million people are at risk of IDD in our country. IDD is endemic in India with 303 districts out of 365 districts surveyed reporting Total Goiter Rate(TGR) >10%.…”
mentioning
confidence: 99%